ELECTRICITY METER WITH THE FACILITY TO DETERMINE THE QUALITY OF THE ELECTRICITY SUPPLIED - DAN ROTAR; GEORGE CULEA (Journal of Engineering Studies and Research)
Many areas of activity face the problem of electricity quality. At the same time, diagnosing the quality of the energy provided makes it possible to identify and remedy problems that have arisen in the system. Advanced signal processing techniques and the use of advanced systems allow for a complex analysis of the phenomenon. The paper presents an electricity meter equipped with an electricity quality analysis system. It was developed based on the Xilinx Artix-7 programmable logic matrix. A Digilent Arty A7 development board was used due to its design and experimentation facilities. The developed system determines the power consumed and the main elements that define the quality of electricity: harmonics and other deviations from the frequency of nominal power supply, flicker, voltage gaps, voltage variations, transient surge, temporary surge, etc. The possibility of using an embedded system equipped with the Microblaze soft microprocessor, the existence of a 12-bit analog-digital converter and the maximum sampling frequency of 1 MSPS and the possibility of assisted design allows to obtain a measurement system with superior characteristics. The results obtained and the experiments carried out confirm the expected performance for the electricity meter.